Developing criteria for selecting freestyle wrestling coaches at international levels - Rangraz, H.; Deshpande, S. S.; Soltani, H. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: The objective of this research was to design and develop criteria for selecting freestyle wrestling coaches at international levels and determining the degree of these criteria importance with respect to coaches and wrestlers` point of view. Material: The research method was of descriptive-survey type. The sample population of this study included 79 freestyle wrestlers and 87 freestyle wrestling coaches selected from 381 participants at wrestling world championship competition in 2013 by classified random sample technique. The measuring instrument was researcher-made questionnaire with 56 variables, evaluated by Delphi method (a = 0.879); internal validity of the questionnaire was assessed by a number of experts who have a long term coaching experience at high levels in wrestling. Statistical methods, used for analysis of data, were descriptive and inferential statistics (Friedman Test, Kruskal-Wallis Test and One Sample Kolmogorov-Smirnov Test). Results : The results of this study indicated that there was no significant difference among coaches and wrestlers on significance level of 8 main criteria for selecting national freestyle wrestling coaches (P>0.05), but they had some differences in the order of dimensions` significance. Conclusion: Psychological skills such as Personality traits and characteristics of motivational as well as scientific knowledge and Management Skills have been considered as a very important criterion, so Wrestling Federations should pay considerable attention to these dimensions .